2018
DOI: 10.1021/acsaem.8b00655
|View full text |Cite
|
Sign up to set email alerts
|

Improved Conductivity of Spark Plasma Sintered Ho-Substituted BaZrO3 Electrolyte Ceramics for IT-SOFCs

Abstract: The effect of spark plasma sintering (SPS) on Ho-substituted BaZrO3 electrolyte ceramics was investigated to enhance the electrical conductivity for intermediate temperature solid oxide fuel cells (IT-SOFCs). The cubic crystal system with Pm3̅m space group symmetry, unit cell parameters, and bond length were revealed through the Rietveld refined X-ray diffraction (XRD) pattern. The microstructure of BaZr0.9Ho0.1O3−δ (BZH10) and BaZr0.8Ho0.2O3−δ (BZH20) SPS samples was found to be highly dense and exhibits the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…But, according to theoretical studies, the Ho-substituted BaZrO 3 may support to progress the conductivity and explore the new substituent for BaZrO 3 regarding proton-conducting electrolyte since the ionic radius of Ho 3+ (90.1 pm) is very similar to that of Y 3+ (90 pm) 34 . However, the study about Ho-substituted BaZrO 3 has been little consideration in the scientific world so far [34][35][36] . In this work, we adopted Ho as a single substituent for BaZrO 3 ceramics to explore the influence of Ho 3+ on the electrical properties of BaZrO 3 ceramics for operative SOFC applications.…”
mentioning
confidence: 99%
“…But, according to theoretical studies, the Ho-substituted BaZrO 3 may support to progress the conductivity and explore the new substituent for BaZrO 3 regarding proton-conducting electrolyte since the ionic radius of Ho 3+ (90.1 pm) is very similar to that of Y 3+ (90 pm) 34 . However, the study about Ho-substituted BaZrO 3 has been little consideration in the scientific world so far [34][35][36] . In this work, we adopted Ho as a single substituent for BaZrO 3 ceramics to explore the influence of Ho 3+ on the electrical properties of BaZrO 3 ceramics for operative SOFC applications.…”
mentioning
confidence: 99%
“…In general, a net εr value arises in dipolar, electronic, ionic, and interfacial polarization of the charge carriers. At low frequencies, primarily electric dipolar and interfacial polarizations are responsible for a frequency-dependent εr behavior [12,16]. Eventually, in the plots in Figure 6, a recurring εr value is decreasing rapidly on raising frequency up to 10 1 Hz in a microscopic region-1 in a prominently interfacial polarization.…”
Section: Dielectric Propertiesmentioning
confidence: 92%
“…Eventually, in the plots in Figure 6, a recurring εr value is decreasing rapidly on raising frequency up to 10 1 Hz in a microscopic region-1 in a prominently interfacial polarization. In the next regime-2, it retards decreasing smoothly up to 1 kHz in an account of a electric dipolar relaxation, which explains that at low frequencies the dipoles coherently follow the frequency of applied electric field but at higher frequencies, they lag behind in response to the external field in effect becomes insignificant at these frequencies [16,17]. At further higher frequencies, an intrinsic electronic polarization is responsible for a steady εr value independent of frequency.…”
Section: Dielectric Propertiesmentioning
confidence: 96%
“…Furthermore, our research group previously investigated Ho-doped BaZrO3 system and found 91.1% relative density for BaZr0.8Ho0.2O3-δ sintered at 1600 ℃ for 8 h with 1.11×10 -3 S-cm -1 total conductivity at 650 ℃ in 3% humidified atmosphere [25]. Similarly, Saini et al reported 99.1% relative density for spark plasma sintered BaZr0.8Ho0.2O3-δ with 9.64×10 -2 S-cm -1 total conductivity at 700 ℃ in 3% humidified atmosphere [26]. Thus, it is concluded that doping of Y 3+ and Ho 3+ in BaZrO3 helps to enhance the electrical conductivity of BaZrO3 while doping of Nd 3+ in BaZrO3 helps to improve the sinterability of BaZrO3.…”
Section: Introductionmentioning
confidence: 92%